Genetic variation and population structure of the rice accessions maintained in the AfricaRice genebank using DArTseq - Gouda, A.C.; Sangare, J.R.; Gnikoua, K.; Wambugu, P.; Huggins, T.D.; Ndjiondjop, Marie-Noelle (2025)
Utilizing the full potential of rice collections mainly depends on an in-depth exploration and understanding of the vast diversity in its germplasm. The AfricaRice genebank holds the largest collection of rice germplasm originating from the African continent. In the present study, we comprehensively characterized a collection of 9013 accessions, including Oryza barthii A. Chev., Oryza glaberrima Steud., Oryza longistaminata A. Chev. & Roehr., Oryza sativa L. ssp. indica, and Oryza sativa L. ssp. japonica, for genetic diversity and population structure using genotyping-by-sequencing through DArTseq analysis. We identified 27,718 high-quality single nucleotide polymorphism markers after the genotypic data were filtered. Based on the analyses, the collection has extensive genetic diversity, and the average genetic distance of the entire set was 0.267 (range 0.001–0.469), with 45.1% of pairs of accessions being highly distant and 40.1% moderately distant from each other. Neighbor-joining tree, principal component, and Bayesian population structure analyses clustered the 9013 accessions into six groups, based roughly on their taxonomic and biological status. The first, second, and third groups consisted of accessions belonging to O. glaberrima, O. barthii, and O. longistaminata, respectively. The fourth, fifth, and sixth groups were improved-indica, japonica, and traditional-indica accessions, respectively. The highest value of genetic variance proportion (PhiPT) was found in the species group followed by groups based on cluster analysis and on Bayesian population structure at K = 6. These results allow us to better understand the genetic diversity present in 9013 rice accessions maintained in the AfricaRice genebank and offer a valuable tool for pre breeding, breeding, and further genetic applications.